AAGBS Annual Report 2021: AAGBS KPI & PI achievements (thrust 1) - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2021)
Thrust 1 dean by leader Prof. Dr. Syed Jamal Abdul Nasir Syed Mohamad